Single-nucleus RNA-seq identifies transcriptional heterogeneity in multinucleated skeletal myofibers - Petrany, Michael J.; Swoboda, Casey O.; Sun, Chengyi; Chetal, Kashish; Chen, Xiaoting; Weirauch, Matthew T.; Salomonis, Nathan; Millay, Douglas P. (Nature communications, 2020)
While the majority of cells contain a single nucleus, cell types such as trophoblasts, osteoclasts, and skeletal myofibers require multinucleation. One advantage of multinucleation can be the assignment of distinct functions to different nuclei, but comprehensive interrogation of transcriptional heterogeneity within multinucleated tissues has been challenging due to the presence of a shared cytoplasm. Here, we utilized single-nucleus RNA-sequencing (snRNA-seq) to determine the extent of transcriptional diversity within multinucleated skeletal myofibers. Nuclei from mouse skeletal muscle were profiled across the lifespan, which revealed the presence of distinct myonuclear populations emerging in postnatal development as well as aging muscle. Our datasets also provided a platform for discovery of genes associated with rare specialized regions of the muscle cell, including markers of the myotendinous junction and functionally validated factors expressed at the neuromuscular junction. These findings reveal that myonuclei within syncytial muscle fibers possess distinct transcriptional profiles that regulate muscle biology. Mammalian skeletal muscle is composed of multinucleated myofibers, containing hundreds of nuclei that coordinate cellular function. Here, the authors show that single-nucleus RNA-sequencing reveals rare and emergent myonuclear populations, and uncovers dynamic transcriptional heterogeneity in development and aging.